Standardization and application of fluorescence in situ hybridization (FISH) in research and diagnostic human cytogenetics - Brusnicky, Jeanette (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. in Med. Sc.) -- University of Stellenbosch, 1996.